2010
DOI: 10.1016/j.ejcts.2010.01.035
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised multicentre clinical comparison of a minimised perfusion circuit versus conventional cardiopulmonary bypass☆☆☆

Abstract: Lack of device-related complications combined with a significant reduction in postoperative atrial fibrillation and transfusion requirements have shown the ROCsafeRX MPC to be both safe and efficient for large-scale use in cardiac patients. Additional data are expected to confirm these initial findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…As mentioned above, the importance of nonelective presentation cannot be overemphasized, 4 with emergency status and hemodynamic instability conferring a uniform high risk. 21 Reduction in cardiac arrhythmias with routine arrhythmia prophylaxis has shown promise. 18Y20 In this large data set, however, reoperation was a very important risk factor (ranking similarly to renal failure and cardiogenic shock), and a uniform and similar negative effect was observed across the procedural types.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the importance of nonelective presentation cannot be overemphasized, 4 with emergency status and hemodynamic instability conferring a uniform high risk. 21 Reduction in cardiac arrhythmias with routine arrhythmia prophylaxis has shown promise. 18Y20 In this large data set, however, reoperation was a very important risk factor (ranking similarly to renal failure and cardiogenic shock), and a uniform and similar negative effect was observed across the procedural types.…”
Section: Discussionmentioning
confidence: 99%
“…CPB can impact upon the cellular and non-cellular elements of blood resulting in the activation of different pro-inflammatory cascades (Anselmi, et al, 2004;Hill, 1998;Khoynezhad, Jalali, & Tortolani, 2004;Rinder, 2006;Suleiman, Zacharowski, & Angelini, 2008). It is now generally accepted that CPB is a direct trigger of cardiac injury since miniaturized cardiopulmonary bypass is associated with less cardiac injury compared to conventional bypass (El-Essawi, et al, 2010;Nguyen, et al, 2014;Remadi, Rakotoarivelo, Marticho, & Benamar, 2006;Skrabal, Steinhoff, & Liebold, 2007). More importantly, miniaturized cardiopulmonary bypass is associated with less inflammatory response (Remadi, et al, 2006;Skrabal, et al, 2007;van Boven, Gerritsen, Waanders, Haas, & Aarts, 2004).…”
Section: Systemic Inflammatory Response During Surgerymentioning
confidence: 95%
“…In another randomized trial, Skrabal et al (Skrabal et al 2007) reported lower myocardial damage with lower levels of creatine-kinase MB and troponine T in patients operated on with MECC system. In a prospective randomized multicenter study (El-Essawi et al 2010), comparing MECC system with conventional ECC, the Authors found statistical differences in need of total transfusion and blood product transfusion. Moreover a lower incidence rate of postoperative atrial fibrillation was detected in MECC group.…”
Section: Miniaturized Extracorporeal Circulation and Isolated Cabg Opmentioning
confidence: 99%
“…The oxygenator of the MECC circuit is one of the most important components of the circuit itself. Oxygenators have the oxygenation membrane of either microporous polypropylene (El-Essawi et al 2010;Wippermann et al 2005) or polymethylpentene (Anastasiadis et al 2011;Puehler et al 2010;Formica et al 2009;Remady et al 2006;). In the latter case the membrane is considered as a diffusion membrane Usually the oxygenator has an integrated heat exchanger and one of the largest gas exchange surface areas, reaching about 2.4 m 2 .…”
Section: Anatomy Of the Miniaturized Extracorporeal Circulation Systemmentioning
confidence: 99%